A randomized controlled study to evaluate the effects of lifestyle intervention program for patients with severe mental illness taking Second Generation Antipsychotics (SGAs) in body weight management and monitoring their Body Mass Index (BMI) - Daniel Yung-fai Cho; Kwan-tai Leung; Fanny So-man Ip; Kei-man Ng; Wing-sum Yuen; Ka-yan Lai; Wanda Luen-wun Siu (Colegio de Enfermería de Caceres, 2022)
Background: Second generation antipsychotics (SGAs) are strongly associated with accelerated body weightgain resulting in overweight and obesity in patients with severe mental illness (SMI). Evidence found that lifestyleinterventions used behavioral techniques to improve dietary habits and increase physical activity can reduce the increasein patients' body weight and BMI. Methods: Randomized Controlled Trial (RCT) on 54 patients with severe mental illnesswere randomized with 27 patients joined in the Lifestyle Intervention group (LIP) and 27 patients in treatment as usual group(TAU) from September/2018 to October/2019. The intervention group attended the educational talks on medication, dietcontrol and physical exercise and use of a daily record. Result: After twelve months, the LIP presented a decrease of 1.25kg(CI 95% -0.73 to 3.24) and treatment as usual TAU presented with a significant increase of 1.65kg CI 95% -2.84 to -0.45)(p=0.009). The BMI of the LIP showed a decrease of 0.51kg/m2 (CI 95% -0.29 to 1.33) and the TAU presented an increaseof 0.66kg/m2. Conclusion: The TAU shows a significant increase of body weight while the LIP group had a decrease inbody weight under the Life Intervention program. This study was not intended for patients to reduce body weight, rather toprevent their body weight to increase and enhance their quality of life through understanding physical health, exercise anddietary habit.